Niveles de vigorosidad de plantaciones de teca, (Tectona grandis), mediante índices de vegetación, en cantón Buena Fe, año 2020. - Plaza Duarte, Henry (2020)
Teak, Tectona grandis, is a timber species introduced in Ecuador with high commercial value. It extends throughout the Ecuadorian coast in more than fifty thousand hectares. Since a few years ago, descending death of trees that start with symptoms of loss of vigor have been reported in several plantations. Some preliminary investigations announce the presence of several fungi as the main causal agent of the disease and Scolitydae insects as possible vectors in the transmission and dissemination of the disease. The Normalized Index of Vegetation, (NDVI), through the use of drones, multispectral cameras and geographic information systems allows to obtain maps that identify sites with greater or lesser Vigor. The characterization of the plantations in strata by the levels of vigor of the trees will allow for appropriate and timely silvicultural management actions that could reduce tree stress levels and improve the quality and health of the trees. The work is aimed at assessing the levels of vigor in a Tectona grandis (teak) plantation, using vegetation indices NDVI. The work evaluated the vigorousness levels in a 17.95 hectare Tectona grandis (teak) plantation at ages four, seven and ten years, by means of the NDVI vegetation index compared to sampling data from plots installed in the field. Similar trends were obtained in the levels of lower and higher vigor both in the results of the aerial photo and the data taken in the field. Vegetation indices obtained from the images and compa data showed acceptable correlations with dasometric variables such as basal area. Keywords: dieback, fungi, insects, aerial photography, sampling plots, silvicultural management. xi